Uncovering the emotional labour of involvement and co-production in mental health research. Issue 4 (21st April 2023) - Faulkner, Alison; Thompson, Rose
Abstract: This article explores the emotional labour of involvement and co-production in mental health research as experienced by service user/survivor researchers and research managers. It is based on a consultation aiming to explore some of the emotional implications raised by bringing lived experience into mental health research, through interviewing people with experience on all sides of the challenges raised. The aim was to develop a research proposal on the basis of the issues raised. Our analysis identified themes describing the negotiation of identity, the emotional work of using and embodying lived experience, and aspects of the working environment. This consultation highlights the intersectional complexities of identity and alienation experienced by people who bring their lived experience of mental distress or using services into unprepared workplaces. It also sheds light on the structural factors that mitigate against the successful integration of lived experience into mental health research. Points of interest: In this article, we explore the emotional implications of being known to have experience of mental distress within the workplace and being expected/expecting to use this experience in your role as researcher. The following themes were identified from interviews: the need to negotiate a 'mental illness' identity alongside an identity as researcher; the emotional work needed to use lived experience in research; the emotional implications of being known to have experience of mental distress and of being expected to use that experience as part of your role as researcher; the implications of competitive working environments; and strategies for managing these complex experiences. We highlight the additional challenges affecting people from Black and minority ethnic communities working in predominantly white workplaces. We highlight the hierarchical and competitive features of academic institutions that prohibit the successful integration of lived experience into mental health research.